Nursing Care of Pregnant Women with Pregnancy Induce Hypertension who Receive General Anesthesia for Cesarean Section at Srisongkram Hospital : Two Comparative Case Studies: การพยาบาลหญิงตั้งครรภ์ที่มีภาวะความดันโลหิตสูงที่ได้รับการระงับความรู้สึกทั่วร่างกายเพื่อผ่าตัดคลอดที่โรงพยาบาลศรีสงคราม: เปรียบเทียบกรณีศึกษา 2ราย - takira, nanjira (Journal of Nursing and Health Sciences Nakhon Phanom University, 2024)
Objective : To study a comparative study of nursing pregnant women with pregnancy induce hypertension who Receive General Anesthesia for caesarean section at Srisongkram Hospital. The results of the study were applied to the practice of systemic anesthesia among pregnant women with preeclampsia for caesarean section at Srisongkram Hospital. Results : From the comparative study of nursing care in both case studies, it was found that: Case Study 1 Chronic hypertension with superimposed preeclampsia while waiting for delivery, non-reassuring fetal status. Case Study 2 preterm and preeclampsia. Both case studies terminated the pregnancy by caesarean section under general anesthesia., and nursing care during and after standard anesthesia. By nurse anesthesiologists trained according to the Royal College of Anesthesiologists. Intubation can be done at once. No serious complications occur both during and after anesthesia. Conclusions: General anesthesia in pregnant women with pregnancy induce hypertension. There is a chance of serious complications threatening the life of the pregnant woman and the fetus. So The nurse anesthetist should be knowledgeable about the disease. Treatment and medications received by the patient before administering anesthesia. This includes knowledge of altered anatomy in pregnant women, which results in a difficult risk of intubation. As well as regular intubation skills training to gain expertise. And they can apply their knowledge to the care of patients in the early stages. While and after administering anesthesia safely. And severe complications can be prevented.